Networks and Contested Identities in the Refugee Journey - Kandasamy, Niro (2022)
This thematic issue traverses refugee research that recognises the importance of networks in determining the paths that refugees undertake in their journeys to seek safety and protection. In recent years, scholars have increasingly pointed to the multifaceted nature of networks in the refugee journey. These articles demonstrate the importance of elucidating the distinct influences and factors that shape refugee networks, including the unequal power relations between refugees and refugee aid workers in transit countries, transnational family and community connections, the proliferation of technologies in strengthening refugees’ networks, the role of the state in privileging certain refugee groups over others, and the role of refugees themselves in mobilising both past and existing networks to activate supports.